2019
DOI: 10.1080/21645515.2019.1697109
|View full text |Cite
|
Sign up to set email alerts
|

Maternal influenza vaccination relates to receiving relevant information among pregnant women in Japan

Abstract: Maternal vaccination for seasonal influenza is currently not listed as a routine vaccination in the national vaccination schedule of Japan. However, many pregnant women voluntarily receive an influenza vaccination. We explored the factors related to influenza vaccine uptake. We particularly focused on factors related to any recommendation, such as advice or suggestions from another individual. We conducted a cross-sectional web-based questionnaire survey in Japan among pregnant women or mothers who had recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…[30][31][32][33][34][35][36] The articles were published from 2010 to 2020. Eleven articles were from the USA, 30,32,35,41,45,46,48,59,60,65,66 six from Australia, [49][50][51]53,61,63 four from France, 31,43,47,57 two from Canada, 56,62 two from the UK 40,55 and one each from Belgium, 54 Brazil, 33 Greece, 44 Hong Kong, 64 Ireland, 52 Japan, 42 Nicaragua, 58 Singapore 34 and Spain. 36 The main characteristics of the included studies are summarized in Tables 1 and S2.…”
Section: Re Sultsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] The articles were published from 2010 to 2020. Eleven articles were from the USA, 30,32,35,41,45,46,48,59,60,65,66 six from Australia, [49][50][51]53,61,63 four from France, 31,43,47,57 two from Canada, 56,62 two from the UK 40,55 and one each from Belgium, 54 Brazil, 33 Greece, 44 Hong Kong, 64 Ireland, 52 Japan, 42 Nicaragua, 58 Singapore 34 and Spain. 36 The main characteristics of the included studies are summarized in Tables 1 and S2.…”
Section: Re Sultsmentioning
confidence: 99%
“…Yamamoto et al showed that pregnant Japanese women who obtained information from medical staff were prevalent among folic acid takers among pregnant Japanese women with a mean age of 33 years in Osaka [ 13 ]. Using an Internet marketing survey of pregnant Japanese women with a mean age of 32 years, Shono et al showed that the main source of information recommending maternal influenza vaccination was an obstetrician, followed by nurses/midwives among vaccinated takers [ 14 ]. Globally, some studies reported similar findings that healthcare professionals are the most common information sources used by women with children.…”
Section: Discussionmentioning
confidence: 99%
“…Increased maternal age, underlying obstetric and gynecologic illnesses, and infant's birth month (October–December) were associated with higher rates of vaccination against seasonal influenza among pregnant women in Japan 27–29 . In Japan, the coverage rates for the H1N1 vaccine during the 2009 H1N1 influenza outbreak were higher (74.0%–95.8%) 32,33 than those for the seasonal influenza vaccine 13,27–31 . More than 60.0% of pregnant Japanese women received the H1N1 vaccine within 1.5 months after its availability, reducing the infection rate by 89.0% without any cases of mortality 34 …”
Section: Coverage Of Maternal Vaccinationmentioning
confidence: 99%
“…10 According to the World Health Organization (WHO), nonviable/inactivated vaccines (e.g., seasonal influenza; COVID-19; and diphtheria, tetanus, and pertussis [DTP] vaccines) can be safely administered to pregnant women; however, viable vaccines (e.g., measles, mumps, and rubella [MMR] vaccine) are contraindicated. 11,12 In Japan, vaccination against seasonal influenza is voluntary (except for individuals aged >65 years) 13 and considered to be safe during all stages of pregnancy as the vaccines are nonviable. 14 The vaccination of pregnant women against COVID-19 is endorsed by the Ministry of Health, Labour and Welfare (MHLW), Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation